STRENGTHENING THE ROLE OF PARENTS IN ACCOMPANYING ELEMENTARY SCHOOL STUDENTS TO USE GADGETS DURING THE COVID-19 PANDEMIC - Eka Oktavianingsih (Widyagogik, 2021)
The school from home (SFH) policy during the COVID-19 pandemic has an impact on the routine activities of elementary students at home. Prior to COVID-19, the time spent by elementary school children using gadgets ranged from 1 to 2 hours per day, while during SFH elementary students could spend at least 4 hours per day. The increasing intensity and frequency of gadget use among elementary school students makes the role of parents important in accompanying children. Of course, the role of parents is needed so that children can use gadgets wisely to support educational goals, not just for entertainment purposes. The purpose of this study is to strengthen the role of parents in assisting elementary school children to use gadgets during the COVID-19 pandemic through outreach and mentoring activities. The subjects involved were 30 parents who have elementary school children in Porodeso Village, Sekaran District, Lamongan Regency. The method of implementation uses face-to-face techniques (with health protocols), door to door, and online (online using whatsapp group). Based on the results of interviews with parents after participating in the program, it shows that most parents have understood and implemented the gadget assistance material for children. The principles of gadget assistance for elementary school children include: exemplary, agreement, consistency, and serenity.